Equinodermos (Echinodermata) del Caribe Mexicano - Laguarda-Figueras, Alfredo (2005)
Echinoderms (Echinodermata) of the Mexican Caribbean. A systematic list of the echinoderms of the Mexican Caribbean based on museum specimens of the Colección Nacional de Equinodermos, Instituto de Ciencias del Mar y Limnología, Universidad Nacional Autónoma de México and the National Museum of Natural History, Smithsonian Institution, Washington, D.C. is presented. This list reveals an important echinoderm biodiversity in the Mexican Caribbean, where five of the six echinoderm classes are represented. A total of 178 echinoderm species is recorded, distributed in 113 genera, 51 families and 22 orders. 30 new records for the Mexican Caribbean are presents: Crinoidea (three), Asteroidea (two), Ophiuroidea (eleven), Echinoidea (one), Holothuroidea (thirteen). Rev. Biol. Trop. 53(Suppl. 3): 109-122. Epub 2006 Jan 30.